Ett enat Kina och ett splittrat NATO - En analys av Frankrike respektive USA's syn på Kinesiska intentioner - Hamrén,Dan; Homrighausen,Alexander (2023)
The situation in the South China Sea region is apparently tense and has been for a long time. However, the reactions of various world powers have been different in visible concern about escalation between two of the area's more central players, China and Taiwan. This work is based on Keren Yahri-Milo's theories and work on intentions and how perceptions of intentions from a state can vary from observer to observer. Initially, the background to the conflict and various elements of its nature are presented, then to present those of Yahri-Milo's theories that are used to answer the research question: Are there indications that show or explain a discrepancy in the US and France's perception of China and its intentions towards Taiwan or not? This is done with a focus on the USA's and France's apparently different perceptions of China's intentions, or at least their attitude towards them. In this essay, the authors state that three of the theories Yahri-Milo presents as explanatory models for intention perception cannot answer the research question. These are the: Capability thesis, Strategic Military Doctrine thesis, and the Behavior thesis. On the other hand, the other three hypotheses, all positioned under the same umbrella theory, the selective attention theory, does submit some clues as to why the US and France might understand China differently. The Vividness, Subjective Credibility, and Organizational expertise-hypotheses all aid the essay in answering the research question well. We find that the discrepancy might be due to organizational biases, personal biases, needs and wants, as well as relevance of information and personal impression.
Keywords: Yarhi-Milo; Selective attention thesis; Conflict; China; France; USA